EXPLORING CHINA’S RESPONSE TO THE ROHINGYA CRISIS: A LIBERAL PERSPECTIVE - Yuan, Changrui; Lee, Brice Tseen Fu (UI Scholars Hub, 2023)
This paper examines China's response to the Rohingya crisis in Myanmar from a theoretical perspective, drawing on both liberal and Asian cultural values. The study adopts a qualitative approach and employs document analysis to collect data. The findings suggest that China's response to the crisis can be explained by the liberal values of interdependence, cooperation, and institutionalism, which have guided China's peaceful and cooperative approach to resolving the conflict. However, the study also reveals the importance of Asian cultural values, particularly empathy and save-face, in shaping China's diplomatic behavior towards the crisis. The paper argues that China's response to the Rohingya crisis can be divided into three aspects: infrastructure investment, mediation between Myanmar and Bangladesh, and humanitarian assistance, all aimed at promoting collaboration and peace in the region. The study contributes to the understanding of the complexities involved in China's foreign policy decisions and provides insights into the role of cultural values in shaping international relations.